2011
DOI: 10.1016/j.cej.2010.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of ethyl pyruvate using gas–liquid slug flow in microchannel

Abstract: a b s t r a c tThe use of a gas-liquid slug flow in a microreactor has several advantages such as a large surface area for contacting gas and liquid phases and circulation flow inside slugs. These advantages accelerate the mass transfer between the two phases, resulting in a high concentration of dissolved gas. The enhanced mass transfer is useful in carrying out liquid phase oxidation that uses oxygen gas as the oxidizing agent. The gas-liquid slug flow in a microreactor system is applied to the oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
(12 reference statements)
0
23
0
1
Order By: Relevance
“…The thin liquid films prevent the viscous polymer solution from adhering to the channel wall and clogging of the channel . Furthermore, it is well‐known that internal circulation flow generated in a slug flow enhances the mixing of reactants in each slug and facilitates mass transfer between the liquid–liquid interfaces . Although a few studies using a slug flow for polymerization have been reported, to the best of our knowledge, there are no studies showing the production of polymer particles using a slug flow.…”
Section: Introductionmentioning
confidence: 99%
“…The thin liquid films prevent the viscous polymer solution from adhering to the channel wall and clogging of the channel . Furthermore, it is well‐known that internal circulation flow generated in a slug flow enhances the mixing of reactants in each slug and facilitates mass transfer between the liquid–liquid interfaces . Although a few studies using a slug flow for polymerization have been reported, to the best of our knowledge, there are no studies showing the production of polymer particles using a slug flow.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Yasukawa et al studied the oxidation of ethyl lactate to pyruvate over various homogeneous vanadium compounds in a gas–liquid microflow system. 16 They found that vanadium oxytrichloride (VOCl 3 ) gave the highest yield (31%) at room temperature, making it 5 times as active as V 2 O 5 . 17 Considering catalyst recovery and product purification, solid vanadium catalysts are preferable.…”
Section: Introductionmentioning
confidence: 99%
“…The recirculation in the liquid slugs improves radial mixing [12,13]. Thus, microreactors operated under Taylor flow have found great use in various chemical processes such as nanoparticle synthesis [14][15][16][17] and homogeneously/heterogeneously catalyzed gas-liquid reactions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%